The poison throne - Kiernan, Celine (New York, NY : Orbit, 2010)
Wynter Moorehawke returns to court with her dying father to find the king has become a violent despot, his son, Alberon has fled into exile and Alberon's half-brother, Razi has been elevated to king. Wynter must choose between her father or her dreams, her friend or her king, her duty or her love.
Keywords: Exiles -- Fiction; Courts and courtiers -- Fiction